In-situ carbon-coated iron electrode and preparation method and application thereof

CN122991999APending Publication Date: 2026-10-27HUNAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611148778.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]但铁-空气电池在充放电过程中存在一些不足,严重阻碍了它的实际应用,主要包括(1)铁电极在放电过程中发生氧化反应,容易在其表面形成钝化物,从而阻碍了电极的进一步充放电;(2)铁电极在充放电时的反应物与产物的体积差异较大,易导致电极结构破坏;(3)铁电极的氢析副反应会造成铁活性物质损失

Benefits of technology

本发明提供了一种原位碳包覆的铁电极的制备方法,包括下列步骤:S1、硫化亚铁与三硫化二铋混合,研磨,得到混合颗粒,随后加入硝酸铁溶液进行搅拌,得到硝酸铁前驱体分散液;S2、向硝酸铁前驱体分散液中加入g-C3N4-CNTs复合物,搅拌,得到混合体;调节混合体pH至4.5-5.5,继续搅拌,得到活性物质前驱体;S3、在保护气氛下,将活性物质前驱体进行煅烧、研磨,得到铁电极活性样品;S4、将铁电极活性样品与聚四氟乙烯乳液混合后涂敷于预处理的泡沫镍表面,干燥、压制,得到原位碳包覆的铁电极。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122991999A_ABST
    Figure CN122991999A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of new energy storage battery, in particular to an in-situ carbon-coated iron electrode and a preparation method and application thereof. The present application mixes a ferric nitrate solution in which ferrous sulfide and bismuth trisulfide are dispersed with a g-C3N4-CNTs compound having a three-dimensional space structure, adjusts the pH to 4.5-5.5, and then forms a ferric hydroxide precipitate dispersed in the space structure of the g-C3N4-CNTs compound. Finally, the ferric hydroxide is decomposed into ferric oxide by pyrolysis, and the latter is tightly attached to the inside of the space structure of the g-C3N4-CNTs compound. The volume shrinkage occurs when the ferric hydroxide is converted into ferric oxide, so that there is a surplus buffer space inside the g-C3N4-CNTs compound, which improves the stability of the charging and discharging process of the electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of novel energy storage battery technology, and in particular to an in-situ carbon-coated iron electrode, its preparation method, and its application. Background Technology

[0002] There are numerous types of novel electrochemical energy storage batteries based on iron electrodes, all demonstrating good potential for practical applications. Among them, iron-air batteries, with their advantages of high specific capacity, dendrite-free charging and discharging processes, abundant iron resources, and the most mature extraction technology, are one of the most promising metal-air batteries in electrochemical energy storage technology.

[0003] However, iron-air batteries have some shortcomings during the charging and discharging process, which seriously hinder their practical application. These mainly include (1) the iron electrode undergoes an oxidation reaction during the discharge process, which easily forms passivation on its surface, thus hindering the further charging and discharging of the electrode; (2) the volume difference between the reactants and products during the charging and discharging of the iron electrode is large, which easily leads to the destruction of the electrode structure; (3) the hydrogen evolution side reaction of the iron electrode will cause the loss of iron active materials.

[0004] Therefore, solving the above problems is the key to the practical application of iron-air batteries. Summary of the Invention

[0005] The purpose of this invention is to provide an in-situ carbon-coated iron electrode, its preparation method and application. By controlling the microstructure of the iron electrode and using a large number of uniformly distributed interfaces to suppress passivation and hydrogen evolution side reactions, the electrochemical performance of the iron electrode is greatly improved, solving the problems of easy formation of passivation layer during iron electrode discharge, existence of hydrogen evolution side reactions, and easy destruction of electrode structure.

[0006] To achieve the above objectives, the present invention provides a method for preparing an in-situ carbon-coated iron electrode, comprising the following steps: S1. Ferrous sulfide and bismuth trisulfide are mixed and ground to obtain mixed particles. Then, ferric nitrate solution is added and stirred to obtain ferric nitrate precursor dispersion. S2. Add g-C3N4-CNTs complex to the ferric nitrate precursor dispersion, stir to obtain a mixture; adjust the pH of the mixture to 4.5-5.5, continue stirring to obtain the active substance precursor; S3. Under a protective atmosphere, the active material precursor is calcined and ground to obtain an iron electrode active sample. S4. The active iron electrode sample is mixed with polytetrafluoroethylene emulsion and then coated onto the pretreated nickel foam surface. After drying and pressing, an in-situ carbon-coated iron electrode is obtained.

[0007] In this invention, the mass ratio of ferrous sulfide to bismuth trisulfide in S1 is 0.5-1.5:0.5-1.5, preferably 1:1. The concentration of the ferric nitrate solution is 0.05-0.15 mol / L, preferably 0.1 mol / L; the mass-to-volume ratio of the mixed particles to the ferric nitrate solution is preferably (2-10) mg:1.25 mL.

[0008] In this invention, the volume-to-mass ratio of the ferric nitrate precursor dispersion to the g-C3N4-CNTs complex in S2 is preferably 50 mL:(200-700) mg.

[0009] In this invention, the preparation process of the g-C3N4-CNTs composite in step S2 is as follows: g-C3N4 nanosheets are mixed with CNTs (carbon nanotubes), ethanol is added, followed by ultrasonic treatment, filtration, drying, and grinding to obtain the g-C3N4-CNTs composite. In the g-C3N4-CNTs composite, the mass ratio of g-C3N4 to CNTs is 0.5-1.5:0.5-1.5, preferably 1:1.

[0010] This invention utilizes the two-dimensional sheet structure of porous ultrathin g-C3N4 nanosheets and the one-dimensional structure of CNTs, and forms a g-C3N4-CNTs composite with a three-dimensional spatial structure after ultrasonic treatment. This invention does not have special requirements for the g-C3N4 nanosheets; they can be purchased or prepared in-house.

[0011] In this invention, the method of adjusting the pH of the mixture in S2 is to add ammonia water to the mixture; the concentration of the ammonia water is preferably 0.5 mol / L.

[0012] In this invention, after stirring in S2, the precipitate is preferably filtered, washed, and dried to obtain the active substance precursor.

[0013] In this invention, the protective atmosphere in S3 is preferably nitrogen; the calcination temperature in S3 is 480-520℃, preferably 500℃, the holding time is 2.5-3.5h, preferably 3h, and the heating rate is 2.5-3.5℃ / min, preferably 3.0℃ / min.

[0014] In this invention, the pretreatment process of the nickel foam in step S4 includes: sequentially ultrasonicating the nickel foam in hydrochloric acid, water, and a mixed solvent; the mixed solvent is composed of acetone and ethanol. The concentration of the hydrochloric acid is 0.4-0.6 mol / L, preferably 0.5 mol / L, and the volume ratio of acetone to ethanol is 0.5-1.5:0.5-1.5, preferably 1:1.

[0015] In this invention, the mixing method in S4 is ultrasonic; the drying temperature is 55-65℃, preferably 60℃, and the time is 5-7h, preferably 6h; the pressing pressure is 580-620kN, preferably 600kN, and the time is 4-6s, preferably 5s.

[0016] This invention does not have any special requirements for the frequency of ultrasound; any frequency known to those skilled in the art can be used.

[0017] The present invention also provides an in-situ carbon-coated iron electrode prepared by the above preparation method.

[0018] The present invention also provides the application of the above-mentioned in-situ carbon-coated iron electrode in the field of energy storage batteries.

[0019] The present invention has the following beneficial effects: This invention provides a method for preparing an in-situ carbon-coated iron electrode, comprising the following steps: S1, ferrous sulfide and bismuth trisulfide are mixed and ground to obtain mixed particles, and then ferric nitrate solution is added and stirred to obtain a ferric nitrate precursor dispersion; S2, g-C3N4-CNTs complex is added to the ferric nitrate precursor dispersion and stirred to obtain a mixture; the pH of the mixture is adjusted to 4.5-5.5 and stirring is continued to obtain an active material precursor; S3, the active material precursor is calcined and ground under a protective atmosphere to obtain an active iron electrode sample; S4, the active iron electrode sample is mixed with polytetrafluoroethylene emulsion and coated onto a pretreated nickel foam surface, dried and pressed to obtain an in-situ carbon-coated iron electrode.

[0020] This invention first disperses ferrous sulfide and bismuth trisulfide in a ferric nitrate solution, then mixes them with a g-C3N4-CNTs complex with a three-dimensional spatial structure, adjusting the pH to 4.5-5.5 to allow ferric hydroxide precipitate to grow in situ and be confined within the pores of the three-dimensional conductive network. After pyrolysis, the ferric hydroxide decomposes into ferric oxide, which is tightly anchored within the g-C3N4-CNTs framework. More importantly, by utilizing the volume shrinkage effect during the conversion of ferric hydroxide to ferric oxide, a buffer cavity is reserved between the ferric oxide particles and the carbon framework, thereby effectively absorbing the volume expansion stress during charge and discharge, significantly improving the stability of the electrode structure.

[0021] The g-C3N4-CNTs composite has a three-dimensional spatial structure. During the formation of iron oxide, it constructs a three-dimensional carbon coating layer in situ on the outer layer of iron oxide particles, thereby avoiding the destruction of the electrode structure due to volume expansion during the charging and discharging process. At the same time, through the in-situ doping of ferrous sulfide and bismuth trisulfide, a large number of interfaces that inhibit anodic passivation and hydrogen evolution reaction are uniformly formed on the surface of iron oxide particles, thereby greatly improving the charge-discharge cycle stability of the iron electrode and the utilization rate of the active material of the iron electrode.

[0022] This invention achieves in-situ doping and uniform dispersion of ferrous sulfide and bismuth trisulfide on the surface of iron oxide by controlling the microstructure of the iron electrode. This effectively constructs an active interface that suppresses anodic passivation and hydrogen evolution side reactions, significantly improving the electrochemical performance of the iron electrode. At the same time, the preparation method provided by this invention is simple and easy to industrialize, which has practical application significance for the development of various novel electrochemical energy storage batteries based on iron electrodes, including iron-air batteries.

[0023] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0024] Figure 1 These are the results of the cyclic charge-discharge test of the iron electrode prepared in Example 1 of this invention; in, Figure 1 Figure A shows the relationship between the specific capacity and the potential of the iron electrode at different cycles for the iron electrode prepared in Example 1. Figure 1 In Figure B, the graph shows the relationship between the specific capacity and the number of cycles of the iron electrode prepared in Example 1. Figure 2 These are the cyclic charge-discharge test results of the iron electrode prepared in Example 2 of this invention; in, Figure 2 Figure A shows the relationship between the specific capacity and the potential of the iron electrode at different cycles for the iron electrode prepared in Example 2. Figure 2 B in the figure represents the relationship between the specific capacity and the number of cycles of the iron electrode prepared in Example 2. Figure 3 These are the cyclic charge-discharge test results of the iron electrode prepared in Example 3 of this invention; in, Figure 3 Figure A shows the relationship between the specific capacity and the potential of the iron electrode at different cycles for the iron electrode prepared in Example 3. Figure 3 B in the figure represents the relationship between the specific capacity and the number of cycles of the iron electrode prepared in Example 3. Detailed Implementation

[0025] The present invention will be further described below with reference to the accompanying drawings and embodiments. Unless otherwise defined, the technical or scientific terms used in this invention should be understood in their ordinary sense by those skilled in the art. The features mentioned above or in the specific examples mentioned in this invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the invention and are not intended to limit the scope of the invention.

[0026] The preparation process of the g-C3N4-CNTs complex used in the following examples is as follows: (1) Place 20g of dicyandiamide powder into a covered crucible and transfer it into a tube furnace. Under a nitrogen atmosphere, heat the mixture from room temperature (18-25℃) to 500℃ at a heating rate of 2℃ / min. Hold the mixture at this temperature for 4 hours and then allow it to cool naturally to room temperature (18-25℃) to obtain primary g-C3N4 nanosheets. (2) The above primary g-C3N4 nanosheets were placed in an open crucible, transferred to a muffle furnace, heated to 500°C at a heating rate of 5°C / min, held for 2 hours and then naturally cooled to room temperature to obtain g-C3N4 nanosheets. (3) Take 500 mg of the g-C3N4 nanosheets prepared above and mix with 500 mg of CNTs (carbon nanotubes), add 50 mL of ethanol and sonicate for 1.5 h, filter the system and dry at 40 °C for 6 h, and grind to obtain g-C3N4-CNTs complex.

[0027] Pretreatment of nickel foam: Place the nickel foam in 0.5 mol / L hydrochloric acid, sonicate for 30 min, wash with pure water until neutral, then sonicate in pure water for 10 min, then sonicate in a mixed solvent (acetone and ethanol in a volume ratio of 1:1) for 10 min, finally wash with pure water, and dry for later use.

[0028] Example 1 S1. Mix 40 mg of ferrous sulfide and 40 mg of bismuth trisulfide, and ball mill at 400 r / min for 6 h to obtain mixed particles. Then add 50 mL of 0.1 mol / L ferric nitrate solution and stir to obtain ferric nitrate precursor dispersion. S2. Add 200 mg of g-C3N4-CNTs complex to 50 mL of ferric nitrate precursor dispersion and stir at 200 r / min for 30 min to obtain a mixture. Add 5 mol / L ammonia water to the mixture to adjust the pH to 5.0 and continue stirring for 2 h. Filter the precipitate formed by stirring, wash it with water 4 times, and place it in a vacuum drying oven to dry at 50 °C for 24 h to obtain the active substance precursor. S3. The active material precursor obtained above is placed in a tube furnace and heated to 500°C at a heating rate of 3°C / min under a nitrogen atmosphere. After holding at this temperature for 3 hours, it is naturally cooled to room temperature. The calcined product is then ground to obtain an iron electrode active sample. S4. Mix the active iron electrode sample with polytetrafluoroethylene emulsion at a mass ratio of 85:15, sonicate, and then coat it onto the pretreated nickel foam surface. Dry at 60°C for 6 hours and press under 600 kN pressure for 5 seconds to obtain an in-situ carbon-coated iron electrode.

[0029] Example 2 S1. Mix 100 mg of ferrous sulfide and 100 mg of bismuth trisulfide, and ball mill at 400 r / min for 6 h to obtain mixed particles. Then add 50 mL of 0.1 mol / L ferric nitrate solution and stir to obtain ferric nitrate precursor dispersion. S2. Add 450 mg of g-C3N4-CNTs complex to 50 mL of ferric nitrate precursor dispersion and stir at 200 r / min for 30 min to obtain a mixture. Add 5 mol / L ammonia water to the mixture to adjust the pH to 5.0 and continue stirring for 2 h. Filter the precipitate formed by stirring, wash it with water 4 times, and place it in a vacuum drying oven to dry at 50 °C for 24 h to obtain the active substance precursor. S3. The active material precursor obtained above is placed in a tube furnace and heated to 500°C at a heating rate of 3°C / min under a nitrogen atmosphere. After holding at this temperature for 3 hours, it is naturally cooled to room temperature. The calcined product is then ground to obtain an iron electrode active sample. S4. Mix the active iron electrode sample with polytetrafluoroethylene emulsion at a mass ratio of 85:15, sonicate, and then coat it onto the pretreated nickel foam surface. Dry at 60°C for 6 hours and press under 600 kN pressure for 5 seconds to obtain an in-situ carbon-coated iron electrode.

[0030] Example 3 S1. Mix 200 mg of ferrous sulfide and 200 mg of bismuth trisulfide, and ball mill at 400 r / min for 6 h to obtain mixed particles. Then add 50 mL of 0.1 mol / L ferric nitrate solution and stir to obtain ferric nitrate precursor dispersion. S2. Add 700 mg of g-C3N4-CNTs complex to 50 mL of ferric nitrate precursor dispersion and stir at 200 r / min for 30 min to obtain a mixture. Add 5 mol / L ammonia water to the mixture to adjust the pH to 5.0 and continue stirring for 2 h. Filter the precipitate formed by stirring, wash it with water 4 times, and place it in a vacuum drying oven to dry at 50 °C for 24 h to obtain the active substance precursor. S3. The active material precursor obtained above is placed in a tube furnace and heated to 500°C at a heating rate of 3°C / min under a nitrogen atmosphere. After holding at this temperature for 3 hours, it is naturally cooled to room temperature. The calcined product is then ground to obtain an iron electrode active sample. S4. Mix the active iron electrode sample with polytetrafluoroethylene emulsion at a mass ratio of 85:15, sonicate, and then coat it onto the pretreated nickel foam surface. Dry at 60°C for 6 hours and press under 600 kN pressure for 5 seconds to obtain an in-situ carbon-coated iron electrode.

[0031] Test Example 1 The in-situ carbon-coated iron electrode prepared in Example 1 was used as the working electrode, and a three-electrode system consisting of a carbon rod and a mercury-mercury oxide electrode as the counter electrode and reference electrode, respectively, was subjected to cyclic charge-discharge testing.

[0032] Cyclic charge-discharge tests were conducted at room temperature using 8 mol / L KOH as the electrolyte. Within a voltage window of -2.0 V to -0.1 V (vs. Hg / HgO), the electrolyte was charged at 5 C and discharged at 1 C. Graphs showing the relationship between specific capacity and iron electrode potential at different cycle counts, as well as the relationship between specific capacity and cycle count, were obtained. (See details below.) Figure 1 As shown.

[0033] from Figure 1 It can be seen that the iron electrode prepared in Example 1 maintains a discharge capacity of about 100 mAh / g at a discharge rate of 1C, and still maintains good stability when the number of charge-discharge cycles reaches 100.

[0034] Test Example 2 The in-situ carbon-coated iron electrode prepared in Example 2 was used as the working electrode, and a three-electrode system consisting of a carbon rod and a mercury-mercury oxide electrode as the counter electrode and reference electrode, respectively, was subjected to cyclic charge-discharge testing.

[0035] Cyclic charge-discharge tests were conducted at room temperature using 8 mol / L KOH as the electrolyte. Within a voltage window of -2.0 V to -0.1 V (vs. Hg / HgO), the electrolyte was charged at 5 C and discharged at 1 C. Graphs showing the relationship between specific capacity and iron electrode potential at different cycle counts, as well as the relationship between specific capacity and cycle count, were obtained. (See details below.) Figure 2 As shown.

[0036] from Figure 2 It can be seen that the iron electrode prepared in Example 2 has a discharge capacity of about 370 mAh / g after the 40th cycle when the discharge rate is 1C; although the discharge capacity fluctuates to some extent in the later stage of the cycle, it still remains at a high value.

[0037] Test Example 3 The in-situ carbon-coated iron electrode prepared in Example 3 was used as the working electrode, and a three-electrode system consisting of a carbon rod and a mercury-mercury oxide electrode as the counter electrode and reference electrode, respectively, was subjected to cyclic charge-discharge testing.

[0038] Cyclic charge-discharge tests were conducted at room temperature using 8 mol / L KOH as the electrolyte. Within a voltage window of -2.0 V to -0.1 V (vs. Hg / HgO), the electrolyte was charged at 5 C and discharged at 1 C. Graphs showing the relationship between specific capacity and iron electrode potential at different cycle counts, as well as the relationship between specific capacity and cycle count, were obtained. (See details below.) Figure 3 As shown.

[0039] from Figure 3 It can be seen that the iron electrode prepared in Example 3 has a discharge capacity of about 340 mAh / g after the 30th cycle when the discharge rate is 1C; the discharge capacity in the later stage of the cycle only fluctuates slightly and still remains at a high value.

[0040] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A method for preparing an in-situ carbon-coated iron electrode, characterized in that, Includes the following steps: S1. Ferrous sulfide and bismuth trisulfide are mixed and ground to obtain mixed particles. Then, ferric nitrate solution is added and stirred to obtain ferric nitrate precursor dispersion. S2. Add g-C3N4-CNTs complex to the ferric nitrate precursor dispersion, stir to obtain a mixture; adjust the pH of the mixture to 4.5-5.5, continue stirring to obtain the active substance precursor; S3. Under a protective atmosphere, the active material precursor is calcined and ground to obtain an iron electrode active sample. S4. The active sample of the iron electrode is mixed with polytetrafluoroethylene emulsion and then coated onto the surface of pretreated nickel foam. After drying and pressing, an in-situ carbon-coated iron electrode is obtained.

2. The method for preparing an in-situ carbon-coated iron electrode according to claim 1, characterized in that, The mass ratio of ferrous sulfide to bismuth trisulfide in S1 is 0.5-1.5:0.5-1.

5.

3. The method for preparing an in-situ carbon-coated iron electrode according to claim 1, characterized in that, The concentration of the ferric nitrate solution is 0.05-0.15 mol / L; The mass-to-volume ratio of the mixed particles to the ferric nitrate solution is (2-10) mg: 1.25 mL.

4. The method for preparing an in-situ carbon-coated iron electrode according to claim 1, characterized in that, The volume-to-mass ratio of the ferric nitrate precursor dispersion to the g-C3N4-CNTs complex in S2 is 50 mL: (200-700) mg; In the g-C3N4-CNTs complex, the mass ratio of g-C3N4 to CNTs is 0.5-1.5:0.5-1.

5.

5. The method for preparing an in-situ carbon-coated iron electrode according to claim 1, characterized in that, The calcination temperature described in S3 is 480-520℃, the holding time is 2.5-3.5h, and the heating rate is 2.5-3.5℃ / min.

6. The method for preparing an in-situ carbon-coated iron electrode according to claim 1, characterized in that, The pretreatment process of the nickel foam described in S4 includes: sequentially ultrasonicating the nickel foam in hydrochloric acid, water, and a mixed solvent; The mixed solvent consists of acetone and ethanol.

7. The method for preparing an in-situ carbon-coated iron electrode according to claim 1, characterized in that, The concentration of the hydrochloric acid is 0.4-0.6 mol / L, and the volume ratio of acetone to ethanol is 0.5-1.5:0.5-1.

5.

8. The method for preparing an in-situ carbon-coated iron electrode according to claim 1, characterized in that, The drying temperature described in S4 is 55-65℃, and the time is 5-7 hours; The pressing pressure is 580-620 kN, and the time is 4-6 seconds.

9. An in-situ carbon-coated iron electrode prepared by the preparation method according to any one of claims 1-8.

10. The application of the in-situ carbon-coated iron electrode as described in claim 9 in the field of energy storage batteries.